2003
DOI: 10.1086/378677
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Cutaneous Leishmaniasis in Outbred Vervet Monkeys, Using a Recombinant Histone H1 Antigen

Abstract: Infection with Leishmania major parasites results in the development of cutaneous ulcerative lesions on the skin. We investigated the protective potential of a single, recombinant histone H1 antigen against cutaneous leishmaniasis in an outbred population of vervet monkeys, using Montanide adjuvant. Protection was assessed by challenging the animals with a mixture of vector sand fly salivary-gland lysate and a low dose of in vitro-derived parasites, thus more closely mimicking natural infection induced by L. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 30 publications
(45 reference statements)
1
33
0
2
Order By: Relevance
“…In malaria, HIV and cancer vaccine studies, MISA 720 has been indicated to induce high Th1 immune responses important for the control of these diseases (KENNEY & ELDELMAN, 2003). This adjuvant has also been shown to induce strong Th1 cytokine in Leishmania vaccination studies (MASINA et al, 2003;MUTISO et al, 2010b). The strong correlation between DTH and both TNF-α and IFN-γ responses in the present study indicates the importance of the DTH response as an early marker of the outcome of a vaccination study.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In malaria, HIV and cancer vaccine studies, MISA 720 has been indicated to induce high Th1 immune responses important for the control of these diseases (KENNEY & ELDELMAN, 2003). This adjuvant has also been shown to induce strong Th1 cytokine in Leishmania vaccination studies (MASINA et al, 2003;MUTISO et al, 2010b). The strong correlation between DTH and both TNF-α and IFN-γ responses in the present study indicates the importance of the DTH response as an early marker of the outcome of a vaccination study.…”
Section: Discussionsupporting
confidence: 65%
“…Following initial immunization, daily observation of immunized animals was carried out and we did not observe any local or systemic side effects in any of the animals immunized with MPLA+Ag or MISA+Ag. The safety of MISA has been reported elsewhere including in vaccination studies carried out in our laboratory (TOLEDO et al, 2001;MASINA et al, 2003;OLIVEIRA et al, 2005). Our safety report on MISA as an adjuvant for Leishmania vaccine differs from other studies that have associated this adjuvant with adverse reactions including swelling and erythema at the injection site observed within a few days following vaccination (PIERCE et al, 2010).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Neste caso, poderse-ia apostar em uma vacina eficiente e operacional, proporcionando ou não imunidade esterilizante. Apesar da abundância de estudos neste sentido, e de alguns resultados otimistas [41][42][43][44][45][46][47][48][49] , não se espera, a curto prazo, a disponibilização deste importante instrumento, continuando a ser problemá-tico o controle da endemia com este perfil de transmissão. Neste caso, a oferta de um sistema de saúde eficiente no diagnóstico e condução clínica dos casos, seria uma alternativa para abrandar os agravos causados pela endemia.…”
Section: Perspectivas De Controleunclassified
“…When Leishmaniasis accompanied by deficient cellular immunity, the disease can improve to chronic shape (Von Stebut 2007;Douba et al 2012).The number of new cases of cutaneous leishmaniasis is estimated a range from 0.7 to 1.2 million.The HIV (human immunodeficiency virus) and Leishmania co infection is reason of rapidly growing of Leishmaniasis in regions where Leishmania species are endemic. In the other hand toxicity of chemotherapy and currently available drugs for treatment haven't shown ideal consequence and ever important, resistance to current drugs, above all things underline to need for a safe, effective vaccine (Coler and Reed 2005;Masina et al 2003). In recent years with completion of genome sequencing of L. major, researchers find out that some of genes are expressed in the infectious stages of the parasite and in particular, in amastigotes, which can help to design effective vaccines (khamesipour et al 2006).…”
Section: Introductionmentioning
confidence: 99%